PENGARUH MODEL PROJECT BASED LEARNING (PjBL) PADA KONSEP SISTEM KOORDINASI MANUSIA TERHADAP KETERAMPILAN METAKOGNITIF SISWA KELAS XI SMA NEGERI 4 BANJARMASIN - Aulia Mahfuzah; Siti Ramdiah (Florea : Jurnal Biologi dan Pembelajarannya, 2020)
Quality education is needed to support the creation of intelligent people who are able to compete in the era of globalization. However, based on a number of international, national, to regional assessments and facts that are encountered directly in the field, students provide information that student awareness in learning is still lacking. This information shows that the cognitive learning outcomes of students have not been maximized. This study aims to determine the effect of the PjBL model on the metacognitive skills of the XI MIPA grade students of SMA Negeri 4 Banjarmasin. Metacognitive skills can help students develop thinking skills which further influence student learning outcomes. This type of research is a quasi experiment, with a design model known as non equivalent pretest-posttest control group design. Data collection techniques using essay tests. Assessment of metacognitive skills refers to Corebima (2009). The research data were analyzed by one way ANOVA statistical analysis using SPSS version 24 for windows with a significance level of 5%. The results showed the average value of the experimental class students facilitated by the PjBL model by 85.47 and the control class facilitated by conventional learning by 73.41 with Fcount = 17.616 (p = 0.000 <0.05). Thus, it can be concluded that the Project Based Learning model has a significant positive effect on the metacognitive skills of the 11th grade students of Mathematics and Natural Sciences in SMA Negeri 4 Banjarmasin